Alcohol protective behavioral strategies in Argentinean college students - Angulo Pereira, Rebeca (2019)
Protective behavioral strategies (PBS) reduce or minimize the negative consequences of alcohol drinking. Previous work, conducted mostly in the U.S., showed that PBS are negatively related to alcohol outcomes and that women exhibited greater use of PBS than men did. The Protective Behavioral Strategies Scale [PBSS] is one of the most used instruments to measure this variable. The present study examined PBS use (as measured by the Protective Behavioral Strategies Scale, PBSS) in 771 freshman college students (62.1% women, M age = 19.61±3.78) from Argentina, and its association with drinking indicators and alcohol-related negative consequences. College freshman that reported alcohol use within the previous month completed an online survey that assessed alcohol use (frequency, quantity, frequency of binge drinking/drunkenness episodes), alcohol-related negative consequences and PBS. Alcohol use was highly prevalent, with 27.1% of women and 40.8% of men reporting having drinking >5 days in the previous month, and 32% (women) to 42% (men) reporting drinking >4 standard drinks of alcohol per drinking session. Women reported significantly higher number of PBS (e.g., stopping drinking at a predetermined time, avoiding drinking games, leaving the party at a predetermined time) than men did (t(769) = 2.96; p ≤ .01). A greater use of PBS was, particularly among women and particularly those describing manners of, was significantly associated with lower alcohol use (i.e., frequency and quantity of alcohol use) and alcohol-related negative consequences. The present findings, which largely replicate those found in the U.S., suggest Argentinean college women exhibited greater use of PBS than men. Despite these sex differences, a greater use of PBS was significantly associated with lower alcohol use and less alcohol-related negative consequences in both, women and men. PBS hold promise as potential targets of interventions aimed at reducing alcohol use and its associated negative consequences.